2022
DOI: 10.1038/s41467-022-28765-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation on cell surface facilitates bFGF signal transduction with heparan sulphate

Abstract: Liquid-liquid phase separation (LLPS) plays important roles in various cellular processes, facilitating membrane-less organelles construction, chromatin condensation, signal transduction on inner membrane and many other processes. Current perception is that LLPS relies on weak multivalent interactions and crowded environments intracellularly. In this study, we demonstrate that heparan sulfate can serve as a platform to induce the phase separation of basic fibroblast growth factor on cell surface. The phase sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“… 111 Xue et al. 135 recently reported basic fibroblast growth factors form condensates with heparan sulphate proteoglycans and activate FGFR signaling pathway. Besides, cytoplasmic scaffolds zonula occludens‐1, zonula occludens‐2, and claudins phase separate to regulate the assembly of tight junctions.…”
Section: Biological Functions Of Biomolecular Condensatesmentioning
confidence: 99%
“… 111 Xue et al. 135 recently reported basic fibroblast growth factors form condensates with heparan sulphate proteoglycans and activate FGFR signaling pathway. Besides, cytoplasmic scaffolds zonula occludens‐1, zonula occludens‐2, and claudins phase separate to regulate the assembly of tight junctions.…”
Section: Biological Functions Of Biomolecular Condensatesmentioning
confidence: 99%
“…Two-dimensional condensates can also be formed on the membrane of the cell or internal organelles [ 70 ]. Recently, the formation of an extracellular condensate between fibroblast growth factor and HSPG has also been observed, which serves to enrich the growth factor around its receptor and trigger signaling transduction [ 70 ].…”
Section: Spla2s Are Globular Proteins But They Can Form Active Conden...mentioning
confidence: 99%
“…Two-dimensional condensates can also be formed on the membrane of the cell or internal organelles [ 70 ]. Recently, the formation of an extracellular condensate between fibroblast growth factor and HSPG has also been observed, which serves to enrich the growth factor around its receptor and trigger signaling transduction [ 70 ]. The same phenomenon can happen with the sPLA2s that interact with HSPGs on the cell surface, and activate an intracellular signal by yet unknown mechanisms, which also triggers their internalization.…”
Section: Spla2s Are Globular Proteins But They Can Form Active Conden...mentioning
confidence: 99%
“…This limits the prospect of LLPS in drug development. Our recent work demonstrated that cytokines like bFGF could undergo LLPS on cell surface with its receptor, which plays important role for effective signal transduction 4 . Inspired by the discovery, we realized that condensing functioning molecules on speci c cells was possible by utilizing LLPS, which can be developed as a powerful biological tool for targeted delivery of massive number of molecules.…”
Section: Introductionmentioning
confidence: 99%